Preparation method of beryllium-copper alloy material with high beryllium content
Through the dual-stage homogenization heat treatment, commutation hot rolling and cyclic "cold rolling-intermediate annealing" process, the problems of uneven second phase components and poor processing performance in high beryllium-content beryllium copper alloy strips are solved, and efficient and stable strip preparation is achieved, improving the yield and production efficiency.
Patent Information
- Application Number
- CN202411798595.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In the prior art, the beryllium copper alloy strips with high beryllium content have problems such as uneven second phase components, cracking, lateral bending, wrinkling, etc. during the heat treatment and processing, resulting in low material yield and low production efficiency.
The distribution and structural structure of the second phase are controlled through the steps of homogenization treatment, the commutation hot rolling process, and the cyclic "cold rolling-intermediate annealing" to ensure the uniformity and forming performance of the strip through steps such as homogenization treatment, hot rolling, annealing and multiple cold rolling annealing.
A uniform second phase component of a beryllium copper alloy strip with high beryllium content is achieved, which reduces the total processing passes, improves production efficiency and material yield, and ensures high performance and stability of the strip.
Smart Images

Figure CN119530580A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper alloys, and in particular relates to a method for preparing a beryllium-copper alloy material with a high beryllium content. Background Art
[0002] Beryllium copper alloy has excellent properties such as high strength, high elasticity, high conductivity, fatigue resistance, and non-pyrophoricity. It is a key material for high-end electronic components in industries such as aerospace, computers, and automobiles. According to the beryllium content, beryllium copper alloys can usually be divided into two categories. One is high beryllium copper alloy, also known as high-strength beryllium copper alloy, with a beryllium content of 1.6 wt%~2.1wt%; the other is low beryllium copper alloy, also known as high-conductivity beryllium copper alloy, with a beryllium content of usually <0.7 wt%. In the actual production process, the beryllium content in low beryllium copper alloy is generally controlled at around 0.4 wt%. Today, the beryllium content of high beryllium copper alloy has been increased to more than 2.5 wt% to obtain better secondary electron emission performance. However, when the Be content exceeds 2.3 wt.%, hard and brittle β / γ phases will be generated in the alloy, causing stress concentration and cracking when the material is deformed, which is not conducive to the forming and processing of beryllium copper alloy strips, limiting the application of beryllium copper alloys in various electronic components; with the increase of Be content, the number of β / γ phases also increases significantly, and the alloy has a greater tendency to crack during processing. Heat treatment process is an important means to regulate the size, morphology and distribution of the second phase. Among them, the heat treatment termination temperature and cooling rate are the key parameters for phase transformation and precipitation of high-B beryllium copper alloys. In addition, due to the presence of the second phase, the work hardening rate of beryllium copper alloy is relatively high, and the pass processing rate and the total number of processing passes significantly affect the production efficiency and yield rate.
[0003] Chinese patent CN202110121201.7 uses a two-stage heat treatment method to obtain an α+β phase beryllium copper alloy. However, the primary heat treatment temperature of this method is higher than the total peritectic reaction temperature of beryllium copper, 863°C, which is easy to form an overburned structure and reduce the performance of the alloy. In addition, the cooling method of this method from the secondary heat treatment temperature to room temperature is not strictly required. If the cooling rate is too slow, the phase transformation and precipitation behavior of the second phase will also occur in the alloy, resulting in reduced workpiece processing performance. Chinese patent CN202311557142.3 uses semi-continuous casting to obtain a beryllium copper alloy ingot, and prepares a beryllium copper alloy strip with a beryllium content of up to 2.5 wt%~5.0 wt% through multiple rolling and intermediate annealing. However, the cooling method after heat treatment in this method is all water cooling, which increases the quenching stress of the workpiece, which is not conducive to subsequent forming processing, and there is a blocky β phase in the alloy, which is easy to form stress concentration in the second phase during processing, resulting in cracking of the workpiece, resulting in a low yield rate of this method. At the same time, this method does not strictly control the rolling deformation, the strip is prone to side bending, wrinkling, etc., and the number of finishing passes is large, which increases the manufacturing cost and has low production efficiency. Therefore, it is of great significance to develop a low-cost, high-production efficiency, high-yield, high-beryllium-content beryllium copper alloy strip preparation method with a stable second phase component for the engineering application of this material. Summary of the invention
[0004] In order to solve the problems of uneven second phase components in the prepared beryllium copper strip, cracking, lateral bending, wrinkling and many processing passes caused by imperfect heat treatment process and rolling pass design in the existing method, the purpose of the present invention is to provide a method for preparing a beryllium copper alloy strip with a high beryllium content.
[0005] In order to achieve the above object, the present invention adopts the following technical solution:
[0006] The invention discloses a preparation method of a beryllium copper alloy material with high beryllium content. The method comprises the following steps: smelting metal raw materials containing pure copper and beryllium copper master alloy to obtain alloy liquid, casting the alloy liquid to obtain ingots, homogenizing the ingots to obtain homogenized cast billets, hot rolling the homogenized cast billets to obtain hot-rolled billets, annealing the hot-rolled billets to obtain annealed billets, cyclically cold rolling-intermediate annealing the annealed billets to obtain alloy strips, and finally finishing rolling and finished product annealing the alloy strips to prepare the beryllium copper alloy material with high beryllium content.
[0007] The preparation method of the invention comprises the following steps: firstly, pure copper and beryllium copper master alloy are smelted and cast to obtain an original ingot, and then a homogenization treatment is performed to effectively solve the material segregation problem, and a beryllium copper alloy with an α+β phase is formed after cooling; then, hot rolling is performed to further densify the billet and eliminate defects, and at the same time, grains are crushed to improve the structure and processing performance to obtain a beryllium copper hot-rolled billet, and then annealing treatment is performed to obtain an annealed billet of the α+γ phase beryllium copper alloy after cooling, and the annealed billet is processed and treated by a cyclic "cold rolling-intermediate annealing" process, and then finishing and finished product annealing treatment is performed to eliminate the residual stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure to obtain a beryllium copper alloy material with a high beryllium content.
[0008] In a preferred embodiment, the high beryllium content beryllium copper alloy material has the following composition, measured in mass percentage: Be: 2.5wt% to 4.0wt%, Mg: 0.00wt% to 2.00wt%, Al: 0.00wt% to 0.50wt%, and the balance is copper.
[0009] Further preferably, the high beryllium content beryllium copper alloy material is composed of the following by mass percentage: Be: 2.8wt% to 3.8wt%, Mg: 1.0wt% to 1.2wt%, Al: 0.06wt% to 0.1wt%, and the balance is copper. With this preferred composition, the high beryllium content beryllium copper alloy generates thicker BeO on the surface after sensitization and activation, and the BeO beryllium oxide film is the main secondary electron emission source, so it has better secondary electron emission performance. After the finished strip is sensitized and activated, the added Mg element generates MgO on the surface, which is also a secondary electron emission source, and cooperates with BeO to emit secondary electrons, thereby further improving the performance. The added Al element generates an aluminum oxide film when the finished strip is sensitized and activated, which wraps BeO and MgO, effectively preventing the secondary electron emission source from failing after being exposed to air, and extending the service life of the workpiece.
[0010] In a preferred embodiment, the metal raw material further comprises copper-magnesium master alloy and pure aluminum.
[0011] Further preferably, the purity of the pure copper is ≥99.99%.
[0012] Further preferably, the beryllium content in the beryllium copper master alloy is 5.0-15.0 wt%.
[0013] Further preferably, the magnesium content in the copper-magnesium master alloy is 10.0-20.0 wt%.
[0014] More preferably, the purity of the pure aluminum is ≥99.99%.
[0015] In the actual operation process, the alloy liquid is obtained by melting in an electric furnace under a protective atmosphere.
[0016] In a preferred solution, the alloy liquid is poured into a crystallizer for semi-continuous casting, and an ingot is obtained after the car body is turned on.
[0017] In a preferred embodiment, the temperature of the homogenization treatment is 800-820° C., and the time of the homogenization treatment is 10-12 hours.
[0018] In the present invention, the homogenization temperature is set below 0.95 times of the peritectic transformation temperature to prevent overburning at the alloy grain boundaries. At the same time, a high temperature of more than 800° C. is maintained to accelerate atomic diffusion, shorten the time required for homogenization, and improve production efficiency.
[0019] Further preferably, after the homogenization treatment is completed, the ingot is first allowed to cool naturally to 650-700°C in a heating furnace, and then the ingot is immediately water-cooled to below 40°C, with a water cooling rate of ≥80°C / s.
[0020] In the present invention, the above cooling method is adopted after homogenization treatment, and the performance of the final obtained material is better, because, on the one hand, the ingot size is usually large, and the cooling rate during air cooling is slow, and it is impossible to ensure that there is no γ phase precipitation in the copper matrix during air cooling; on the other hand, if direct water cooling is adopted at a high homogenization temperature, the cooling water will boil before the ingot is cooled to the eutectoid temperature of 618°C, and the boiling water will significantly reduce the cooling rate of the ingot, resulting in the ingot being unable to reach a cooling rate of 80°C / s when passing through the eutectoid temperature of 618°C, and the alloy will undergo a partial eutectoid reaction β→α+γ when passing through the eutectoid temperature zone, and a small amount of γ phase will precipitate inside the larger cast β phase grains, becoming a crack source during subsequent processing. In the present invention, by first naturally cooling the ingot to 650~700°C in a heating furnace, and then adopting a water-cooling cooling method, it can ensure that the water cooling rate is ≥80°C / s, avoiding the precipitation of γ phase in the alloy during heat treatment and cooling, and obtaining a beryllium copper alloy ingot with a complete α+β phase component.
[0021] The preferred solution is to heat the homogenized ingot to 750°C-780°C and keep the temperature for 30-60 minutes, and then perform hot rolling.
[0022] Further preferably, the homogenized ingot is heated to 750°C-780°C at a heating rate of ≥20°C / s. In the present invention, the homogenized ingot is quickly heated to the holding temperature. If the heating rate is too slow, there will be a precipitate phase in the copper matrix, while the rapid heating will allow the alloy to skip the precipitation temperature range and maintain a complete α+β phase composition.
[0023] In a preferred embodiment, the hot rolling process is: first 4 to 6 passes of reversing hot rolling, and then 3 to 5 passes of unidirectional hot rolling, wherein the deformation amount of the reversing hot rolling passes is 28% to 32%, and the deformation amount of the unidirectional hot rolling passes is 18% to 22%.
[0024] Further preferably, the reversing angle of the reversing hot rolling is 90 degrees.
[0025] The inventors found that the use of reversing hot rolling has a significant effect on the crushing of the second phase, improves the dispersion of the second phase, and inhibits edge cracks during the rolling process. The γ phase changes from lamellar to ellipsoidal particles, reducing the pinning force of the γ phase on the interface. Changing the rolling direction can significantly reduce the anisotropy of the plate, and effectively regulate the strip shape so that it does not bend or wrinkle.
[0026] Preferably, the annealing temperature of the hot-rolled billet is 750° C. to 780° C., and the holding time is 30 to 40 minutes.
[0027] Further preferably, after the annealing treatment is completed, air cooling is performed at a rate of 0.5-5°C / s.
[0028] In the present invention, by controlling the cooling rate after annealing to 0.5-5°C / s, the β phase in the alloy will be completely transformed into α+γ with alternating lamellar distribution, and there is no needle-shaped γ phase in the copper matrix. This organization will show excellent cooperative deformation ability in subsequent processing.
[0029] In a preferred embodiment, during the cold rolling-intermediate annealing cycle of the annealed billet, the intermediate annealing is performed once every 3 to 5 cold rolling passes.
[0030] In a preferred embodiment, during the cold rolling-intermediate annealing cycle of the annealed billet, the deformation amounts of the 3 to 5 cold rolling passes performed before any intermediate annealing are as follows: the deformation amount of the first pass is 10% to 12%, the deformation amount of the second pass is 18% to 25%, and the deformation amount of the third pass and above is 30% to 35%.
[0031] The present invention adopts a cyclic "cold rolling-intermediate annealing" process, and annealing is performed after four cold rolling passes to remove work hardening. The maximum deformation per pass can reach 35%, which significantly reduces the total number of processing passes and has high production efficiency.
[0032] In a preferred embodiment, the cold rolling is performed to a size 0.05 to 0.08 mm larger than the finished material size.
[0033] Preferably, the intermediate annealing temperature is 750° C. to 780° C., and the holding time is 30 to 40 minutes.
[0034] Further preferably, after any intermediate annealing is completed, air cooling is performed, and the air cooling rate is 0.5-5°C / s.
[0035] In actual operation, the strip is cleaned after cold rolling to remove the oxide layer and impurities on the surface. After cold rolling, it is finished by stretching, bending and straightening units and slitting units.
[0036] The preferred solution is to perform 1 to 3 passes of finishing rolling, with each pass deformation being 10% to 15%.
[0037] In a preferred embodiment, the temperature of the finished product annealing treatment is 750°C to 780°C, and the holding time is 10 to 15 minutes.
[0038] Further preferably, after the finished product annealing treatment is completed, air cooling is performed with an air cooling rate of 0.5-5°C / s.
[0039] In a preferred embodiment, the high beryllium content beryllium copper alloy material is selected from one of plate and strip materials, tube and rod materials, and wire materials, preferably plate and strip materials.
[0040] Principles and advantages
[0041] In recent years, beryllium copper alloys with high beryllium content have been widely studied and applied in various electronic components. The second phase containing beryllium elements at high beryllium content is more likely to undergo phase transformation and precipitation behavior during heat treatment and cooling. Its size, morphology and distribution are key factors affecting the production of beryllium copper alloy strips with high beryllium content. Common second phases are blocky β phase and needle-shaped γ phase. The blocky β phase is generated by the reverse eutectoid reaction α+γ→β at 618~620℃. If it is directly cooled from this temperature to below 40℃ at a cooling rate of ≥80℃ / s, a beryllium copper alloy with α+β phase is obtained. There are two ways to generate the needle-shaped γ phase: one is that the alloy is precipitated in the copper matrix after aging at 150~550℃, and the other is that the alloy is cooled at a cooling rate of <80℃ / s and a small amount of eutectoid reaction β→α+γ occurs at 315~620℃. Both γ phases have an adverse effect on the initial processing of the ingot. However, when the cooling rate is 0.5~5℃ / s, the β phase in the alloy will be completely transformed into α+γ with alternating lamellar distribution, and there is no needle-shaped γ phase in the copper matrix. This organization will show excellent cooperative deformation ability in subsequent processing. The present invention mainly utilizes the different cooling rates of ingots and strips, and considers the actual production efficiency. The ingots are cooled by water and the strips are cooled by air, which improves the organizational structure of the material, promotes the reasonable distribution of hard phases in the metal material, avoids the precipitation of harmful hard phases, reduces the deformation resistance of the material, and ensures no cracking and no breakage, thereby improving the yield rate.
[0042] The design of the deformation amount of the rolling pass will directly affect the organization, performance and stability of the material and rolling process. A large deformation amount per pass can refine the internal grains of the material, which helps to improve the strength and toughness of the material, while reducing the number of passes, thereby improving processing efficiency, saving time and process costs; however, excessive deformation will lead to stress concentration, increasing the risk of material cracking or breakage, especially for high-hardness, low-plasticity materials. At the same time, the rolling mill equipment needs to withstand greater rolling forces, which may accelerate equipment wear and even cause equipment failure. A small deformation amount can effectively avoid stress concentration and make the internal stress distribution of the material more uniform, thereby reducing the risk of cracking; however, a small deformation amount per pass is not enough to fully refine the grains, which may make it difficult for the mechanical properties of the material to meet the requirements, and at the same time will lead to an increase in the number of rolling passes, a longer processing cycle, reduced production efficiency, and increased energy consumption and costs. The present invention reasonably designs the deformation amount for hot rolling and cold rolling processes to improve production efficiency on the basis of ensuring the performance and quality of the strip.
[0043] Compared with the prior art, the present invention has the following beneficial effects:
[0044] (1) The second phase components are uniform and consistent:
[0045] Compared with the heat treatment process in the prior art, the first-level homogenization temperature of the present invention is strictly controlled to be less than 0.95 times the peritectic transformation temperature to prevent overburning at the alloy grain boundaries. At the same time, a high temperature of more than 800°C is maintained to accelerate atomic diffusion, shorten the time required for homogenization, and improve production efficiency. The present invention adopts a water-cooling cooling method during ingot homogenization. On the one hand, the ingot specifications and dimensions are usually large, and the cooling rate during air cooling is slow, and it cannot be guaranteed that there is no γ phase precipitation in the copper matrix during air cooling; on the other hand, if direct water cooling at a high homogenization temperature is used, a cooling rate of 80°C / s cannot be achieved. When the alloy passes through the eutectoid temperature zone, a partial eutectoid reaction β→α+γ will occur, and a small amount of γ phase will precipitate inside the larger cast β phase grains, becoming a crack source during subsequent processing. Therefore, the present invention adopts a two-stage homogenization treatment and a water-cooling cooling method to avoid the precipitation of γ phase in the alloy during heat treatment and cooling, and obtain a beryllium copper alloy ingot with a complete α+β phase component;
[0046] (2) The total number of processing passes is small and the production efficiency is high:
[0047] Compared with the rolling process in the prior art, the present invention adopts a hot processing process combining reversing hot rolling and unidirectional rolling, and adopts a large processing pass deformation in the first 4 to 6 passes of reversing hot rolling to reduce the total number of processing passes; the present invention adopts a cyclic "cold rolling-intermediate annealing" process, and annealing is performed after 4 cold rolling passes to remove work hardening. The maximum pass deformation can reach 35%, which significantly reduces the total number of processing passes and has high production efficiency;
[0048] (3) Good deformation performance:
[0049] The invention adopts a two-stage homogenization heat treatment process, a reversing hot rolling process, and a cyclic "cold rolling-intermediate annealing" process to prepare a high beryllium content beryllium copper alloy strip with a uniform second phase. During rolling deformation, the second phase and the copper matrix are deformed in coordination, and the metal rheology is uniform. The periodic annealing process makes the cold-rolled strip soften significantly, and large deformation processing can be achieved under a small tonnage rolling force.
[0050] (4) Few strip defects and high yield rate:
[0051] Compared with the cold rolling process in the prior art, the present invention adopts an air cooling method for the annealing treatment of each level of strips. The strip has a large heat dissipation area and cools faster. No γ phase is precipitated in the copper matrix, and only a eutectic reaction β→α+γ occurs to form a stable α+γ phase beryllium copper alloy with a core-shell structure, which reduces the possibility of edge cracking of the material in the subsequent rolling process and improves the yield rate. At the same time, air cooling reduces the quenching stress of the strip compared to water cooling, which is conducive to obtaining a strip with low anisotropy and improves the yield rate. The present invention adopts a stepped pass deformation design for the continued processing of the annealed strip. The first pass deformation of the annealed strip is small and controlled at 10% to 12%. The annealed strip is shaped with a small deformation to eliminate thickness differences, wrinkles, etc., and then the deformation is increased to roll to the thickness of the finished strip to prepare a high-quality, good-shaped, defect-free beryllium-content beryllium copper strip.
[0052] (5) Good secondary electron emission performance and long-term stability:
[0053] After sensitization and activation, beryllium copper alloy with high beryllium content generates thicker BeO on the surface, and BeO beryllium oxide film is the main secondary electron emission source, so it has better secondary electron emission performance. The role of adding Mg element is that after the finished strip is sensitized and activated, MgO, which is also a secondary electron emission source, is generated on the surface, and it cooperates with BeO to emit secondary electrons, thereby further improving the performance. The role of adding Al element is that when the finished strip is sensitized and activated, an aluminum oxide film is generated, which wraps BeO and MgO, effectively preventing the secondary electron emission source from failing after being exposed to air, and extending the service life of the workpiece. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Figure 1 A schematic flow chart of a method for preparing a beryllium-copper alloy strip with a high beryllium content provided by an embodiment of the present invention;
[0055] Figure 2 It is a schematic diagram of reversing rolling process;
[0056] Figure 3 This is an optical microstructure diagram of the beryllium copper ingot obtained in step S2 of Example 1, wherein the yellowish brown is the α phase, the white phase is the β phase, and it can be seen that there is no precipitate in the β phase;
[0057] Figure 4 This is an optical microstructure diagram of the beryllium copper ingot obtained in step S2 of comparative example 1. Black needle-shaped precipitates appear in the white β phase. In the subsequent processing, the black needle-shaped precipitates will become crack sources;
[0058] Figure 5 This is a photo of the beryllium copper strip obtained in step S6 of Example 1. It can be seen that the surface of the strip is smooth and has no defects such as side bending, wrinkling, and edge cracks;
[0059] Figure 6 This is a photo of the beryllium copper strip obtained in step S6 of comparative example 3. No gradient cold rolling deformation amount is set in the process, resulting in defects such as lateral bending, wrinkling, and cracking in the strip. DETAILED DESCRIPTION
[0060] See also Figure 1 This embodiment provides a method for preparing a beryllium-copper alloy strip with a high beryllium content, which is specifically completed by the following steps:
[0061] S1: Take 99.99% electrolytic pure copper and beryllium copper master alloy with beryllium content of 5.0-15.0 wt%, copper-magnesium master alloy with magnesium content of 10.0-20.0 wt%, and pure aluminum with purity ≥99.99%, and mix them according to the chemical composition of high beryllium copper strip, then smelt them in an inert atmosphere electric furnace to obtain alloy solution, and then cast them into a crystallizer for semi-continuous casting and car skin to obtain original ingots;
[0062] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 800-820°C for homogenization treatment, keeping the temperature for 10-12 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 650-700°C, and then immediately cooling the ingot to below 40°C by water cooling, with a cooling rate of ≥80°C / s, to form a beryllium copper alloy with α+β phase;
[0063] S3: The ingot obtained in step S2 is put into the induction furnace again, heated to 750℃~780℃ at a heating rate of 20~30℃ / s, kept at this temperature for 30~60 minutes, and then hot rolled. The first 4~6 passes are reversing hot rolling, and the reversing angle is 90 degrees. Figure 2 As shown, the first rolling direction is specified as RD1, the second rolling direction is specified as RD2, the third rolling direction is specified as RD1, the fourth rolling direction is specified as RD2, and so on.
[0064] The deformation amount of each pass is 28%~32%, and the subsequent pass is unidirectional hot rolling, and the deformation amount of each pass is 18%~22%, so as to obtain a beryllium copper strip;
[0065] S4: Under a protective atmosphere, the beryllium copper strip is placed in a heating furnace at 750° C. to 780° C., kept at this temperature for 30 to 40 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 0.5 to 5° C. / s to obtain an α+γ phase beryllium copper alloy;
[0066] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 10%-12%, 18%-25%, 30%-35%, 30%-35%, the annealing temperature is 750°C-780°C, the temperature is kept for 30-40 minutes, then the strip is taken out, air-cooled to below 40°C, and the cooling rate is 0.5-5°C / s;
[0067] S6: Circulate step S5 to cold-roll the beryllium copper strip to 0.05-0.08 mm above the finished strip size, and then wash it;
[0068] S7: The cleaned strip is subjected to 1 to 3 passes of finish rolling, with a deformation amount of 10% to 15% per pass, and is finished by a stretching and straightening unit and a slitting unit;
[0069] S8: The finished strip is placed in a heating furnace at 750°C~780°C for 10~15 minutes for finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. It is then taken out and air-cooled to below 40°C at a cooling rate of 0.5~5°C / s to obtain a beryllium copper alloy strip with a high beryllium content.
[0070] Embodiment 1
[0071] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0072] Be: 2.8 wt%,
[0073] Mg: 1.1 wt%,
[0074] Al: 0.1 wt%,
[0075] The balance is copper.
[0076] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 10.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0077] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 820° C. for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 700° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0078] S3: The ingot obtained in step S2 is put into the induction furnace again, heated to 780°C at a heating rate of 30°C / s, kept at this temperature for 60 minutes, and then hot rolled. The first 6 passes are reversing hot rolling, the reversing angle is 90 degrees, and the pass deformation is 32%. The subsequent passes are unidirectional hot rolling, and the pass deformation is 22%, to obtain a beryllium copper strip;
[0079] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 780° C. heating furnace, kept at this temperature for 40 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 5° C. / s to obtain an α+γ phase beryllium copper alloy;
[0080] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 12%, 25%, 35%, and 35%, the annealing temperature is 780°C, the temperature is kept for 40 minutes, then the strip is taken out, and air-cooled to below 40°C, and the cooling rate is 5°C / s;
[0081] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0082] S7: The cleaned strip is subjected to three passes of finish rolling, with a deformation of 15% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0083] S8: The finished strip is placed in a heating furnace with an annealing temperature of 750°C and kept at this temperature for 15 minutes to perform finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 5°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0084] The performance indicators of the alloy plate and strip in this embodiment are: tensile strength 1050 MPa, yield strength 710 MPa, and elongation 12.5%.
[0085] Embodiment 2
[0086] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0087] Be: 3.2 wt%,
[0088] Mg: 1.2 wt%,
[0089] Al: 0.08 wt%,
[0090] The balance is copper.
[0091] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 10.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0092] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 810° C. for homogenization treatment, keeping the temperature for 11 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 680° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0093] S3: The ingot obtained in step S2 is put into the induction furnace again, and the temperature is raised to 750°C at a heating rate of 25°C / s, and the temperature is kept for 40 minutes before hot rolling. The first four passes are reversing hot rolling, the reversing angle is 90 degrees, and the pass deformation is 30%. The subsequent passes are unidirectional hot rolling, and the pass deformation is 20%, so as to obtain a beryllium copper strip;
[0094] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 750° C. heating furnace, kept warm for 30 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 3° C. / s to obtain an α+γ phase beryllium copper alloy;
[0095] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 10%, 20%, 30%, and 35%, the annealing temperature is 750°C, the temperature is kept for 30 minutes, then the strip is taken out, air-cooled to below 40°C, and the cooling rate is 3°C / s;
[0096] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0097] S7: The cleaned strip is subjected to two passes of finish rolling, with a deformation amount of 10% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0098] S8: The finished strip is placed in a heating furnace with an annealing temperature of 780°C and kept at this temperature for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 3°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0099] The performance indicators of the alloy plate and strip in this embodiment are: tensile strength 1110 MPa, yield strength 750 MPa, and elongation 10.3%.
[0100] Embodiment 3
[0101] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0102] Be: 3.8 wt%,
[0103] Mg: 1.0 wt%,
[0104] Al: 0.06 wt%,
[0105] The balance is copper.
[0106] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 15.0 wt%, copper-magnesium master alloy with magnesium content of 15 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0107] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 800° C. for homogenization treatment, keeping the temperature for 10 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 650° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0108] S3: The ingot obtained in step S2 is put into the induction furnace again, heated to 750°C at a heating rate of 20°C / s, kept at this temperature for 30 minutes, and then hot rolled. The first four passes are reversing hot rolling, the reversing angle is 90 degrees, and the deformation amount of each pass is 28%. The subsequent passes are unidirectional hot rolling, and the deformation amount of each pass is 18%, so as to obtain a beryllium copper strip;
[0109] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 750° C. heating furnace, kept warm for 30 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 1° C. / s to obtain an α+γ phase beryllium copper alloy;
[0110] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed for 4 passes each time, the deformation amounts of the 4 passes are 10%, 18%, 30%, and 30%, the annealing temperature is 750°C, the temperature is kept for 30 minutes, then the strip is taken out, and air-cooled to below 40°C, and the cooling rate is 1°C / s;
[0111] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0112] S7: The cleaned strip is subjected to two passes of finish rolling, with a deformation amount of 10% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0113] S8: The finished strip is placed in a heating furnace with an annealing temperature of 750°C and kept at this temperature for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 1°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0114] The performance indicators of the alloy plate and strip in this embodiment are: tensile strength 1310 MPa, yield strength 850 MPa, and elongation 7.1%.
[0115] Comparative Example 1
[0116] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0117] Be: 2.7 wt%,
[0118] Mg: 1.4 wt%,
[0119] Al: 0.1 wt%,
[0120] The balance is copper.
[0121] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 10.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0122] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 800°C for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, and then immediately cooling the ingot to below 40°C by water cooling, with a cooling rate of ≥80°C / s;
[0123] S3: The ingot obtained in step S2 is put into the induction furnace again, and the temperature is raised to 750°C at a heating rate of 30°C / s, and the temperature is kept for 60 minutes before hot rolling. The first four passes are reversing hot rolling, the reversing angle is 90 degrees, and the pass deformation is 28%. The subsequent passes are unidirectional hot rolling, and the pass deformation is 22%, and the beryllium copper strip is obtained;
[0124] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 750° C. heating furnace, kept at this temperature for 40 minutes for annealing, then taken out and air-cooled to below 40° C. at a cooling rate of 3° C. / s;
[0125] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 10%, 18%, 30%, and 35%, the annealing temperature is 750°C, the temperature is kept for 40 minutes, then the strip is taken out, and air-cooled to below 40°C, and the cooling rate is 5°C / s;
[0126] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0127] S7: The cleaned strip is subjected to three passes of finish rolling, with a deformation amount of 10% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0128] S8: The finished strip is placed in a heating furnace with an annealing temperature of 750°C for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip and promote recovery and recrystallization. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 5°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0129] The performance indicators of the alloy plate and strip in this comparative example are: tensile strength 910 MPa, yield strength 620 MPa, and elongation 6.3%.
[0130] Comparative Example 2
[0131] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0132] Be: 2.7 wt%,
[0133] Mg: 1.3 wt%,
[0134] Al: 0.15 wt%,
[0135] The balance is copper.
[0136] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 10.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0137] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 800° C. for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, then stopping the heating of the induction furnace, naturally cooling to 700° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0138] S3: putting the ingot obtained in step S2 into the induction furnace again, heating it to 780°C at a heating rate of 20-30°C / s, keeping it at that temperature for 60 minutes, and then hot rolling it, with a deformation amount of 20% per pass, to obtain a beryllium copper strip;
[0139] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 750° C. heating furnace, kept warm for 30 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 3° C. / s to obtain an α+γ phase beryllium copper alloy;
[0140] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 10%, 18%, 30%, and 35%, the annealing temperature is 750°C, the temperature is kept for 30 minutes, then the strip is taken out, air-cooled to below 40°C, and the cooling rate is 5°C / s;
[0141] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0142] S7: The cleaned strip is subjected to three passes of finish rolling, with a deformation amount of 10% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0143] S8: The finished strip is placed in a heating furnace with an annealing temperature of 750°C and kept at this temperature for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 5°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0144] The performance indicators of the alloy plate and strip in this comparative example are: tensile strength 990 MPa, yield strength 680 MPa, and elongation 8.1%.
[0145] Comparative Example 3
[0146] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0147] Be: 2.8 wt%,
[0148] Mg: 1.2 wt%,
[0149] Al: 0.08 wt%,
[0150] The balance is copper.
[0151] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 10.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0152] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 800° C. for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, then stopping the heating of the induction furnace, naturally cooling to 700° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0153] S3: The ingot obtained in step S2 is put into the induction furnace again, and the temperature is raised to 750°C at a heating rate of 30°C / s, and the temperature is kept for 60 minutes before hot rolling. The first 6 passes are reversing hot rolling, the reversing angle is 90 degrees, and the pass deformation is 32%. The subsequent passes are unidirectional hot rolling, and the pass deformation is 18%, and the beryllium copper strip is obtained;
[0154] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 750° C. heating furnace, kept warm for 30 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 3° C. / s to obtain an α+γ phase beryllium copper alloy;
[0155] S5: cold rolling the annealed strip obtained in step S4 for multiple times, with a deformation amount of 24% per pass, annealing after every 6 passes, with an annealing temperature of 750°C, keeping the temperature for 30 minutes, then taking it out, air cooling it to below 40°C, and cooling rate of 4°C / s;
[0156] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0157] S7: The cleaned strip is subjected to two passes of finish rolling, with a deformation amount of 12% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0158] S8: The finished strip is placed in a heating furnace with an annealing temperature of 750°C for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip and promote recovery and recrystallization. The strip is then taken out and air-cooled to below 40°C at a cooling rate of 5°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0159] The performance indicators of the alloy plate and strip in this comparative example are: tensile strength 1010 MPa, yield strength 780 MPa, and elongation 5.3%.
[0160] Comparative Example 4
[0161] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0162] Be: 3.5 wt%,
[0163] Mg: 1.2 wt%,
[0164] Al: 0.06 wt%,
[0165] The balance is copper.
[0166] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 15.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0167] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 820° C. for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 700° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0168] S3: The ingot obtained in step S2 is put into the induction furnace again, and the temperature is raised to 780°C at a heating rate of 25°C / s, and hot rolled after keeping the temperature for 30 minutes. The first five passes are reversing hot rolling, the reversing angle is 90 degrees, and the pass deformation is 29%. The subsequent passes are unidirectional hot rolling, and the pass deformation is 20%, and the beryllium copper strip is obtained;
[0169] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 780° C. heating furnace, kept at this temperature for 30 minutes for annealing, then taken out, and water-cooled to below 40° C., with a cooling rate of ≥80° C. / s, to obtain an α+β phase beryllium copper alloy;
[0170] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 11%, 21%, 30%, and 35%, the annealing temperature is 780°C, the temperature is kept for 30 minutes, then the strip is taken out, and water-cooled to below 40°C, and the cooling rate is ≥80°C / s;
[0171] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0172] S7: The cleaned strip is subjected to two passes of finish rolling, with a deformation amount of 12% per pass, and is finished by a stretch straightening unit and a slitting unit;
[0173] S8: The finished strip is placed in a heating furnace with an annealing temperature of 780°C and kept warm for 10 minutes to perform finished product annealing treatment to eliminate the stress of the strip, promote recovery and recrystallization, and form a uniform and consistent structure. The strip is then taken out and water-cooled to below 40°C with a cooling rate of ≥80°C / s to obtain a beryllium-copper alloy strip with a high beryllium content.
[0174] The performance indicators of the alloy plate and strip in this comparative example are: tensile strength 1260 MPa, yield strength 960 MPa, and elongation 1.9%.
[0175] Comparative Example 5
[0176] This embodiment specifically prepares a beryllium copper alloy strip with a high beryllium content. The beryllium copper alloy with a high beryllium content in this embodiment includes the following components:
[0177] Be: 3.8 wt%,
[0178] Mg: 1.0 wt%,
[0179] Al: 0.09 wt%,
[0180] The balance is copper.
[0181] S1: 99.99% electrolytic pure copper, beryllium copper master alloy with beryllium content of 15.0 wt%, copper-magnesium master alloy with magnesium content of 10 wt% and 99.99% pure aluminum are prepared according to the chemical composition of high beryllium copper strip, and then smelted in an inert atmosphere electric furnace to obtain an alloy solution, which is then cast into a crystallizer for semi-continuous casting and car skin to obtain an original ingot;
[0182] S2: putting the ingot obtained in step S1 into an induction furnace with a protective atmosphere, heating the furnace to 820° C. for homogenization treatment, keeping the temperature for 12 hours to eliminate the segregation of the ingot, then stopping the induction furnace heating, naturally cooling to 700° C., and then immediately cooling the ingot to below 40° C. by water cooling, with a cooling rate of ≥80° C. / s, to form a beryllium copper alloy with α+β phase;
[0183] S3: The ingot obtained in step S2 is put into the induction furnace again, heated to 780°C at a heating rate of 30°C / s, kept at this temperature for 60 minutes, and then hot rolled. The first 6 passes are reversing hot rolling, with a deformation of 32% per pass, and the subsequent passes are unidirectional hot rolling, with a deformation of 22% per pass, to obtain a beryllium copper strip;
[0184] S4: Under a protective atmosphere, the beryllium copper strip is placed in a 780° C. heating furnace, kept at this temperature for 40 minutes for annealing, then taken out, and air-cooled to below 40° C. at a cooling rate of 5° C. / s to obtain an α+γ phase beryllium copper alloy;
[0185] S5: cold rolling the annealed strip obtained in step S4 for multiple times, annealing is performed in 4 passes each time, the deformation amounts of the 4 passes are 12%, 25%, 35%, and 35%, the annealing temperature is 780°C, the temperature is kept for 40 minutes, then the strip is taken out, and air-cooled to below 40°C, and the cooling rate is 5°C / s;
[0186] S6: cyclically cold-rolling the beryllium copper strip to 0.05 mm above the finished strip size, followed by washing;
[0187] S7: The cleaned strip is subjected to three passes of finish rolling, with a deformation amount of 15% per pass, and is finished by a stretching and straightening unit and a slitting unit to obtain a beryllium-copper alloy strip with a high beryllium content.
[0188] The performance indicators of the alloy plate and strip in this embodiment are: tensile strength 1310 MPa, yield strength 1030 MPa, and elongation 1.0%.
[0189]
Claims
1. A method for preparing a beryllium-copper alloy material with a high beryllium content, characterized in that: Metal raw materials including pure copper and beryllium copper master alloy are smelted to obtain alloy liquid, the alloy liquid is cast to obtain ingots, the ingots are homogenized to obtain homogenized cast billets, the homogenized cast billets are hot rolled to obtain hot-rolled billets, the hot-rolled billets are annealed to obtain annealed billets, the annealed billets are cyclically cold rolled-intermediate annealed to obtain alloy strips, and finally the alloy strips are finish rolled and finished product annealing to prepare beryllium copper alloy materials with high beryllium content.
2. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1, characterized in that: The high-beryllium-content beryllium-copper alloy material has the following composition, measured in mass percentage: Be: 2.5 wt% to 4.0 wt%, Mg: 0.00 wt% to 2.00 wt%, Al: 0.00 wt% to 0.50 wt%, and the balance is copper.
3. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1 or 2, characterized in that: The metal raw materials also include copper-magnesium master alloy and pure aluminum; The purity of the pure copper is ≥99.99%; In the beryllium copper master alloy, the content of beryllium is 5.0-15.0 wt%; In the copper-magnesium master alloy, the content of magnesium is 10.0-20.0wt%; The purity of the pure aluminum is ≥99.99%; The alloy liquid is poured into a crystallizer for semi-continuous casting, and an ingot is obtained after the car body is rolled.
4. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1 or 2, characterized in that: The temperature of the homogenization treatment is 800-820°C, and the time of the homogenization treatment is 10-12h; After the homogenization treatment is completed, the ingot is first allowed to cool naturally to 650-700° C. in the heating furnace, and then immediately water-cooled to below 40° C., with a water cooling rate of ≥80° C. / s.
5. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1, characterized in that: The homogenized ingot is heated to 750°C~780°C and kept at this temperature for 30~60 minutes, and then hot rolled; Heating the homogenized ingot to 750°C~780°C at a heating rate of ≥20°C / s; The hot rolling process is: first 4 to 6 passes of reversing hot rolling, then 3 to 5 passes of unidirectional hot rolling, wherein the deformation amount of the reversing hot rolling pass is 28% to 32%, and the deformation amount of the unidirectional hot rolling pass is 18% to 22%; The reversing angle of the reversing hot rolling is 90 degrees.
6. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1 or 5, characterized in that: The temperature of the hot-rolled billet annealing treatment is 750°C to 780°C, and the holding time is 30 to 40 minutes; After the annealing treatment is completed, air cooling is carried out at a rate of 0.5~5℃ / s.
7. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1, characterized in that: During the cold rolling-intermediate annealing cycle of the annealed billet, the intermediate annealing is performed once every 3 to 5 cold rolling passes; During the cold rolling-intermediate annealing cycle of the annealed billet, the deformation amounts of the 3 to 5 cold rolling passes performed before any intermediate annealing are specifically as follows: the deformation amount of the first pass is 10% to 12%, the deformation amount of the second pass is 18% to 25%, and the deformation amount of the third pass and above is 30% to 35%.
8. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1 or 7, characterized in that: The cold rolling is performed to 0.05-0.08 mm above the finished material size; The intermediate annealing temperature is 750°C to 780°C, and the holding time is 30 to 40 minutes; After any intermediate annealing is completed, air cooling is performed at a rate of 0.5~5℃ / s.
9. The method for preparing a beryllium-copper alloy material with a high beryllium content according to claim 1 or 2, characterized in that: Finish rolling 1~3 times, the deformation of each pass is 10%~15%; The temperature of finished product annealing treatment is 750℃~780℃, and the holding time is 10~15min; After the finished product annealing treatment is completed, air cooling is carried out at an air cooling rate of 0.5~5℃ / s.
10. The method for preparing a beryllium copper alloy material with a high beryllium content according to claim 1 or 2, characterized in that: The high beryllium content beryllium copper alloy material is selected from one of plate and strip materials, tube and rod materials, and wire materials.
Citation Information
Patent Citations
A heat treatment process for high beryllium beryllium copper alloys
CN112708837B
Preparation method of C17410 beryllium copper strip
CN112708791A
Preparation method of beryllium copper strip for photomultiplier tube
CN117512388A
Laminated electronic component
JP1993074648A
Cited By
Forming method of beryllium-copper alloy ultrafine wire
CN121696256A
Copper strip for micro curved surface machining and preparation method and application thereof
CN122500055A